Reshaping of the conformational search of a protein by the chaperone trigger factor - Mashaghi Tabari, Alireza; Kramer, Günter; Bechtluft, Philipp; Zachmann-Brand, Beate; Driessen, Arnold J. M.; Bukau, Bernd; Tans, Sander J. (Nature, 2013)
The bacterial chaperone named trigger factor is found to stabilize protein folding intermediates that eventually convert to the native state, suggesting that chaperones play a direct role in instructing protein folding.
Gesehen am 25.06.2021